Twelve years a slave [compact disc, unabridged] - Northup, Solomon, 1808-1863? (Dreamscape Media, 2013)
Twelve Years a Slave is the harrowing account of a black man, born free in New York State, who was drugged, kidnapped, and sold into slavery in 1841. Having no way to contact his family, and fearing for his life if he told the truth, Solomon Northup was sold from plantation to plantation in Louisiana, toiling under cruel masters for twelve years before meeting Samuel Bass, a Canadian who finally put him in touch with his family, and helped start the process to regain his freedom.